Espacialização da estiagem no Rio Grande do Sul de 1981 a 2011: análise da localização e vulnerabilidade de projetos de assentamentos (PA’s) do INCRA - Kulman, Denilson (2015)
Studies and surveys on climate phenomena serve to plan the geographical space. In this sense, research has mainly focused on spatialization of the drought in Rio Grande do Sul from 1981 to 2011 and the location of land reform settlements (PA). The social issue was viewed from the location of land reform settlements and their susceptibility to drought. The steps to performing the research consist of literature review, data surveys in primary and secondary sources, such as INCRA and INPE. For the treatment of information and preparation of final maps, the SPRING and the QGIS software were used, along with Ordinary Kriging geostatistical technique. A fieldwork was also carried out in selected settlements from the location in areas of high drought occurrence in order to verify the susceptibility of the settlers. The results are divided into two parts: use of GIS and geostatistical technique for obtaining the spatial maps of drought occurrence per decade and synthesis map of occurrence for the whole period of analysis and the PA location map per drought occurrence class. The second part is the analysis and discussion of the results obtained in maps and tables with information about the settlements, in order to support the territorial planning.